Molecular characterization, chemical profile and biological properties of essential oils from Chamaemelum nobile (L.) flowers of Morocco: in vitro and in silico studies - El-Assri, El-Mehdi; El-Assri, Youssef; El Brahimi, Rajae; El fadili, Mohamed; Baghouz, Asmae; Abuelizz, Hatem A.; Er-Rahmani, Sara; Lahkimi, Amal; Bouia, Abdelhak (Frontiers in Chemistry, 2025)
IntroductionThis study investigated the antioxidant, antimicrobial, and insecticidal properties of Chamaemelum nobile (L.) essential oil (CN-EO), harvested in Taounate, Morocco. The molecular composition and chemical profile of CN-EO were also characterized.MethodsThe CN-EO was extracted using a Clevenger apparatus. Its chemical composition was analyzed using gas chromatography-mass spectrometry (GC-MS). Antioxidant activity was evaluated using the DPPH assay, while antimicrobial properties were assessed via the disk diffusion method to measure inhibition zones against various bacterial and fungal strains. Insecticidal activity was tested through bioassays to determine insect mortality and repellency rates. Phylogenetic analysis of DNA sequences was conducted to confirm the species identity.ResultsGC-MS analysis identified 24 compounds in CN-EO, with β-Oplopenone (18.66%), Spathulenol (14.90%), and Himachalene (12.47%) as major constituents. CN-EO exhibited strong antioxidant activity (IC50 = 135.8 ± 1.03 μg/mL). Antimicrobial assays revealed inhibition zones of up to 20.67 ± 0.58 mm (Staphylococcus aureus) and antifungal inhibition of 40.42% ± 2.82% against Aspergillus flavus. Insecticidal tests showed total insect mortality at 166 µL/L within 48 h and a 60% repellent effect. Phylogenetic analysis of the DNA sequence revealed a 99.22% similarity with Chamaemelum nobile (L.).ConclusionThese results demonstrate the significant potential of Moroccan CN-EO in phytomedicine. It exhibits a wide range of biological activities and shows great promise as a natural antioxidant, antimicrobial agent, antifungal, and insecticide.